The controlling nutritional status score predicts postoperative mortality in patients with ruptured abdominal aortic aneurysm: a retrospective study - Ye, Sheng-Lin; Xiang, Guang-Yuan; Liu, Zhao; Li, Wen-Dong; Tang, Tao; Qian, Ai-Min; Li, Xiao-Qiang; Sun, Li-Li (Frontiers in Cardiovascular Medicine, 2023)
Background Ruptured abdominal aortic aneurysms (rAAAs) are challenging for vascular surgeons because they have a high mortality rate. In many diseases, nutritional status is closely associated with prognosis. The Controlling Nutritional Status (CONUT) screening tool score is a prognostic factor in some malignant and chronic diseases; however, the impact of nutritional status on rAAA has not yet been reported. In this study, we explored the relationship between the CONUT score and the postoperative prognosis of patients with rAAA. Methods This was a retrospective review of 39 patients with rAAA who underwent surgical treatment from March 2018 to September 2021 at one center. Patient characteristics, nutritional status (CONUT score), and postoperative status were recorded. The patients were divided into groups A and B based on the CONUT score. The baseline characteristics of the two groups were compared, and Cox proportional hazards and logistic regression analyses were used to determine independent predictors of mid-term mortality and complications, respectively. Results The overall mid-term mortality rate was 28.21% (11/39). Compared with group A, group B had higher intraoperative (P = 0.047) and mid-term mortality (P = 0.033) rates. The univariate analysis showed that age [hazard ratio (HR), 1.098; 95% confidence interval (CI), 1.019–1.182; P = 0.014], CONUT score (HR, 1.316; 95% CI, 1.027–1.686; P = 0.03), and surgical procedure (HR, 0.127; 95% CI, 0.016–0.992; P = 0.049) were associated with mid-term mortality, whereas the multivariate analysis showed that the CONUT score (HR, 1.313; 95% CI, 1.009–1.710; P = 0.043) was an independent predictor of mid-term mortality. The multivariate logistic regression analysis did not reveal any associations with complications. The Kaplan–Meier curves showed that group B had a lower mid-term survival rate (log-rank P = 0.024). Conclusion Malnutrition is closely associated with the prognosis of patients with rAAA, and the CONUT score can be used to predict mid-term mortality.